Loss of DCC expression in astrocytomas: relation to p53 abnormalities, cell kinetics, and survival. Issue 11 (1st November 2001) - Hara, A; Saegusa, M; Mikami, T; Okayasu, I
Abstract : Aims —Although frequent reduction or loss of DCC (deleted in colorectal carcinomas) has been demonstrated in gliomas, the association with cell kinetics and survival is still unclear. Methods —A total of 119 astrocytomas, comprising 39 grade IV, 36 grade III, and 44 low grade tumours, were immunohistochemically investigated, along with 26 normal adult brain samples and two fetal brains. The results were compared with p53 abnormalities, Ki-67 labelling index (LI), mitotic index (MI), apoptotic index (AI), and survival. Results —In normal adult and fetal brain tissues, DCC expression was detected in mature and terminally differentiated neuronal cells but not glial elements. In astrocytomas, whereas DCC expression was still clearly shown with low grade malignancy, DCC scores were significantly decreased in high histological grade malignancy, along with an increase in cell kinetics determined by AI, MI, and Ki-67 LI values. In addition, p53 LI values were significantly increased, although a direct link between DCC scores and p53 LI values was not evident. Univariate analysis revealed that high DCC scores and low p53 LI values were closely related to a favourable outcome for astrocytoma, although only the AI was an independent prognostic factor. Conclusions —The loss of DCC expression may be closely related to changes in cell kinetics and tumour phenotype in astrocytomas, independent of p53 abnormalities.